Three decades of EU climate policy: racing toward climate neutrality? - Dupont, Claire; Moore, Brendan; Boasson, Elin Lerum; Gravey, Viviane; Jordan, Andrew; Kivimaa, Paula; Kulovesi, Kati; Kuzemko, Caroline; Oberthür, Sebastian; Panchuk, Dmytro; Rosamond, Jeffrey; Torney, Diarmuid; et al. (Wiley interdisciplinary reviews. Climate change, 2024)
The European Union (EU) began developing climate policy in the 1990s. Since then, it has built up a broad portfolio of mitigation policy measures and governance tools, including legally binding targets to reduce greenhouse gas (GHG) emissions, and policy measures addressing emissions trading, renewable energy, energy efficiency, and more. In 2019, the European Commission—the EU's executive arm—published the European Green Deal (EGD), an overarching policy framework to achieve the goal of climate neutrality by 2050. The EGD aims to push EU climate policy and governance far beyond incremental policy development. In this article, we ask: does the EGD represent a break from past patterns of EU climate governance? We argue that it maintains several past patterns, but nevertheless breaks from other established policy and governance trends. We review insights from politicization and new institutionalist theoretical lenses to help us understand these findings. We reveal certain tensions and challenges inherent in the EU's climate governance approach—around speed and coherence, effectiveness and just transition—that highlight future research needs, and raise questions about the EU's ability to implement its climate policy goals. This article is categorized under: Policy and Governance > Multilevel and Transnational Climate Change Governance
Zuerst veröffentlicht: 15. Oktober 2023
Gesehen am 26.01.2024